TREATMENT OF NATURALLY OCCURRING CANINE EHRLICHIOSIS WITH DOXYCYCLINE, PRECEDED OR NOT BY IMIDOCARB DIPROPIONATE (Revista de Ciências Agroveterinárias, 2004)
Canine ehrliquiosis has become one of most important infectious diseases, especially due to its increasingly prevalence amongst dogs. Many treatment protocols have been proposed, but the association of imidocarb and doxycycline is frequently used because it shows an adequate therapeutic response. However, imidocarb can not be prescribed to some patients, which represents a paradox for many clinicians. The aim of this study was to evaluate the clinical response of doxycycline, preceded or not by imidocarb, for treating canine ehrlichiosis. Two groups of nine dogs were composed: the first was treated with doxycycline, whereas the second was treated with doxycycline and imidocarb. Results showed that both treatments were satisfactory, demonstrating that the clinical response did not depend on the use of imidocarb in the experiment.
Keywords: ehrlichiosis; dog; doxycycline; imidocarb; therapy.